2013
DOI: 10.1093/ejcts/ezt174
|View full text |Cite
|
Sign up to set email alerts
|

The new EuroSCORE II does not improve prediction of mortality in high-risk patients undergoing cardiac surgery: a collaborative analysis of two European centres

Abstract: The new EuroSCORE II does not improve risk prediction in high-risk patients undergoing adult cardiac surgery when compared with original additive and logistic EuroSCOREs. The key problem of risk stratification in high-risk patients has not been addressed by this new model. Future iterations of the score should explore more advanced statistical methods and focus on developing procedure-specific algorithms. Moreover, models that predict complications in addition to mortality may prove to be of increasing value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 24 publications
1
42
2
6
Order By: Relevance
“…An additional limitation of the EuroSCORE is its overestimation of mortality, particularly with higher scores. 1,29 Seventh, a new version of the EuroSCORE (II) was proposed after completing enrollment. 26 We had information on the variables that were newly included in the model with the exception of pulmonary arterial pressure, which was collected as pulmonary hypertension (>60 mm Hg) instead of the categories (31-55 mm Hg and >55 mm Hg) as per the EuroSCORE II.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…An additional limitation of the EuroSCORE is its overestimation of mortality, particularly with higher scores. 1,29 Seventh, a new version of the EuroSCORE (II) was proposed after completing enrollment. 26 We had information on the variables that were newly included in the model with the exception of pulmonary arterial pressure, which was collected as pulmonary hypertension (>60 mm Hg) instead of the categories (31-55 mm Hg and >55 mm Hg) as per the EuroSCORE II.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…The recently published EuroSCORE II [1] refreshed our 17 knowledge of adult cardiac surgical risk and gave us an …”
mentioning
confidence: 99%
“…In another study from Italy (a total of 1090 patients) the accuracy of ESII was also not significantly higher than other scores (logES: AUC 0.79; ESII: AUC 0.81) [8]. The same tendency appeared also in the study of two European centres in Birmingham and Rotterdam on a group of 933 patients [16].…”
Section: Discriminatory Powermentioning
confidence: 56%
“…The outcomes of other studies were not unanimous. Higher results for logES were obtained only in two reports from European institutions with p-values ranging from 0.30 [8] to 0.45 [16]. It is interesting that only in one of the newest performed studies, ESII demonstrated tolerable calibration (p = 0.12) [8].…”
Section: Discriminatory Powermentioning
confidence: 79%